The Role of the Dorsal Striatum in Reward and Decision-Making - Balleine, Bernard W. (J Neurosci, 2007)
Although the involvement in the striatum in the refinement and control of motor movement has long been recognized, recent description of discrete frontal corticobasal ganglia networks in a range of species has focused attention on the role particularly of the dorsal striatum in executive functions. Current evidence suggests that the dorsal striatum contributes directly to decision-making, especially to action selection and initiation, through the integration of sensorimotor, cognitive, and motivational/emotional information within specific corticostriatal circuits involving discrete regions of striatum. We review key evidence from recent studies in rodent, nonhuman primate, and human subjects.